2015
DOI: 10.18325/jkmr.2015.25.2.119
|View full text |Cite
|
Sign up to set email alerts
|

The Retrospective Medical Charts Review of 459 Neck Pain Inpatients in Korean Medicine Hospital

Abstract: Objectives The purpose of this study was to investigate the characteristics of inpatients who were admitted to Korean medicine hospital due to neck pain. Methods Four hundred fifty nine neck pain patients who were admitted to Cheonan Korean Medicine Hospital, Dae-jeon University from 1st, January, 2013 to 31th, December, 2013 were retrospectively reviewed according to medical charts. Results In this study, people in their 30s, females, within 0~2 weeks after onset, motivated by traffic accident, diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Huh et al [31] reported that the number of patients who had received treatments only at Western medicine institutions for neck pain, was the largest among patients who were consequently admitted to Korean medicine hospitals for neck pain. Including the Data are presented as means ± SD.…”
Section: Timing Of Treatmentmentioning
confidence: 99%
“…Huh et al [31] reported that the number of patients who had received treatments only at Western medicine institutions for neck pain, was the largest among patients who were consequently admitted to Korean medicine hospitals for neck pain. Including the Data are presented as means ± SD.…”
Section: Timing Of Treatmentmentioning
confidence: 99%